Wolbachia as an “Infectious” Extrinsic Factor Manipulating Host Signaling Pathways - Negri, Ilaria (Frontiers in Endocrinology, 2012)
Wolbachia pipientis is a widespread endosymbiont of filarial nematodes and arthropods. While in worms the symbiosis is obligate, in arthropods Wolbachia induces several reproductive manipulations (i.e. cytoplasmic incompatibility, parthenogenesis, feminization of genetic males and male-killing) in order to increase the number of infected females. These various phenotypic effects may be linked to differences in host physiology, and in particular to endocrine-related processes governing growth, development and reproduction. Indeed, a number of evidences links Wolbachia symbiosis to insulin and ecdysteroid signalling, two multilayered pathways known to work antagonistically, jointly or even independently for the regulation of different molecular networks. At present it is not clear whether Wolbachia manipulates one pathway, thus affecting other related metabolic networks, or if it targets both pathways, even interacting at several points in each of them. Interestingly, in view of the interplay between hormone signalling and epigenetic machinery, a direct influence of the “infection” on hormonal signalling involving ecdysteroids might be achievable through the manipulation of the host’s epigenetic pathways.